HELMINTHS OF SMALL MAMMALS IN AN ATLANTIC FOREST BIOLOGICAL STATION IN RIO DE JANEIRO, BRAZIL - Gentile, Rosana (2022)
Interface areas between urban and sylvatic environments increase the contact between humans and wild animals, and may favour the transmission of zoonoses. The aim of this study was to describe the helminth fauna of a small mammal community in an urban-sylvatic interface area of the Brazilian Atlantic Forest. Twenty helminth species were recovered in six species of small mammals. Parasite sharing was observed in two helminth species among the marsupials. This study is the first report of a helminth infection for the marsupial Monodelphis americana (Müller, 1776). This is the first report of the nematodes Aspidodera raillieti Travassos, 1913, Viannaia hamata Travassos, 1914 and Trichuris sp. parasitizing the marsupial Marmosa paraguayana (Tate, 1931). None of the helminth species found has been reported to infect humans.